2008
DOI: 10.1021/jp800001t
|View full text |Cite
|
Sign up to set email alerts
|

Thermoreversible Gelation of Poly(Vinylidene Fluoride) in Phthalates:  The Influence of Aliphatic Chain Length of Solvents

Abstract: Thermoreversible gelation of poly(vinylidene fluoride) (PVDF) has been studied in a new series of solvents (phthalates), for example, dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DBP), and dihexyl phthalate (DHP) as a function of temperature and polymer concentration, both by test tube tilting and dynamic light scattering (DLS) method. The effect of aliphatic chain length (n) of diesters on the gelation kinetics, structure/microstructure and morphology of PVDF gels has been examined. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 48 publications
6
38
0
Order By: Relevance
“…Its gelation processes forming α phase in camphor, organic diesters, and phthalates, forming β phase in ethylene carbonate (EC), have been investigated using molecular modeling [91]. Molecular modeling of the PVDF-EC system indicated that electrostatic and Hbonding forces are responsible for fixing the conformation of the β phase ( Fig.…”
Section: Polymorphism During Pvdf Fabrication Via Tips Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Its gelation processes forming α phase in camphor, organic diesters, and phthalates, forming β phase in ethylene carbonate (EC), have been investigated using molecular modeling [91]. Molecular modeling of the PVDF-EC system indicated that electrostatic and Hbonding forces are responsible for fixing the conformation of the β phase ( Fig.…”
Section: Polymorphism During Pvdf Fabrication Via Tips Processmentioning
confidence: 99%
“…Molecular modeling of the PVDF-EC system indicated that electrostatic and Hbonding forces are responsible for fixing the conformation of the β phase ( Fig. 9) [91]. It was believed that the interacting sites of PVDF and the diester were the >CF 2 and >C=O moieties, respectively, between which dipole-dipole-type interactions exist due to electronic polarization.…”
Section: Polymorphism During Pvdf Fabrication Via Tips Processmentioning
confidence: 99%
“…However, the lower q regions are best fitted, represented by solid line (inset figure), with Debye‐Bueche model (Eqn. ), where I(o) is the extrapolated structure factor at zero wavevector and ξ is the correlation length . The correlation length, ξ, essentially the blob dimension has drastically been reduced in nanogel (7.4 nm), thereby explain the term nanogel, as compared to pure gel (30.7 nm) in same solvent.…”
Section: Resultsmentioning
confidence: 99%
“…PVDF gels were prepared in the concentration range 1–30 wt% and gelation kinetics in MEK was studied as a function of polymer concentration by using the tube‐tilting method. In another set of measurements, the effect of temperature on the gelation kinetics was probed in the temperature range −40 to −20 °C for concentrations in the range 17–30 wt% …”
Section: Introductionmentioning
confidence: 99%